STUDIES ON LENGTH FREQUENCY OF OILSARDINE AT CALICUT DURING 1970-71 to 73-74 - Rengaswamy, V S (Indian Journal of Fisheries, 2011)
Studies M Ca’Hcut on ge and growth of c-ilsallXEne Sardinella longiceps hy means of length-frequency method indkated thalt the oilsardine aÂ·ttains the total length of 125-13q mm at the end of one year, 165-175 mm at the end of two years and 180-190 mm on comp et on of three yeÂ·a;rs. From he m01nthly progression of modes during different years, it c()uld be seen that the fishelry was mainly suppoJ1ted by the O-year, l-yea.rand 2-yea1r oJ.a1sses. The Mudies also lfevea<Jed that the growth dul’ing the first y;ear was mOIre al::CelerÂ·Med thaln dur:ng the rest of its Hfe spa,n.